New lanthanide-based complexes constructed from cucurbit[6]uril: Synthesis, structures and properties. Issue 9 (3rd May 2018) - Qiu, Xiumin; Wang, Xin; Hou, Shengzhen; Ma, Haili; Tan, Yebang
Abstract: Three lanthanide-based complexes, {Gd2 (H2 O)10 (CB[6])2 }·CB[6]·6Cl·12H2 O (1 ), {[Gd2 (H2 O)8 CB[6]2 ]·(CuCl4 )·4Cl·46H2 O}n (2 ), and {Dy2 (NO3 )2 (H2 O)10 (CB[6])}·4NO3 ·14H2 O (3 ) (CB[6] = cucurbit[6]uril), were prepared with cucurbit[6]uril (CB[6]). These complexes were characterized by single-crystal X-ray diffraction, elemental analysis, FT-IR spectroscopy, UV–Vis spectroscopy, thermogravimetric analysis and magnetization measurements. Crystallographic results showed that1 and3 are dinuclear and crystallize in the triclinic space group P ī, whereas2 is a 1-D zigzag supramolecular chain that crystallizes in the monoclinic system in C 2/ c . The results indicated that temperature has a big effect on the supramolecular assemblies and a different structure inducer also leads to the formation of different coordination polymers. Frequency dependence in the ac susceptibility signals was observed in3 . Abstract :